From Our Historical Collection: The King’s Speech - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2014)
A seemingly dry, technical paper from 1937 in the Telecommunications Journal of Australia offers much broader interest following the popularity of the 2010 film 'The King’s Speech’. The June 1937 paper by A.H. Kaye describes the engineering networking arrangements set up by the Australian Postmaster General’s Department to transmit across Australia the BBC’s audio commentary on King George VI’s coronation to all Australian national and commercial radio stations. The six hour broadcast included the now famous speech by the newly crowned King to his British Commonwealth.